Method for expanding light absorption range of photocatalytic material and improving photocatalytic hydrogen production performance

By doping rare earth ions Yb3+ and Er3+ into WO3 to form a core-shell composite material, the problem of low solar energy utilization of photocatalytic materials was solved, and efficient photocatalytic hydrogen production under visible and near-infrared light was achieved.

CN119455981AActive Publication Date: 2025-02-18BEIHANG UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411475784.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-02-18
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

Existing photocatalytic materials can only absorb ultraviolet light and short-wave visible light, which cannot fully utilize solar energy. Furthermore, composite materials suffer from problems such as mismatched conduction band positions or unfavorable interface structures, resulting in limited photocatalytic activity.

Method used

By doping rare earth ions Yb3+ and Er3+ into WO3 rich in oxygen vacancies, a core-shell composite material is formed. Through two-photon absorption of WO3 and upconversion luminescence of rare earth ions, photo-photonic and photo-electric synergistic sensitization is achieved, expanding the photoresponse range to the visible and near-infrared regions.

Benefits of technology

It significantly improves the hydrogen production performance of photocatalytic materials under ultraviolet-visible-near-infrared light and increases the utilization rate of photogenerated charge.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455981A_ABST
    Figure CN119455981A_ABST
Patent Text Reader

Abstract

According to the method for expanding the light absorption range of the photocatalytic material and improving the photocatalytic hydrogen production performance, WO3 rich in oxygen vacancies is doped with rare earth ions Yb < 3 + > and Er < 3 + > to achieve up-conversion luminescence, WO3: Yb < 3 + > and Er < 3 + > serve as sensitizers to form a composite material of a core-shell structure with photocatalytic semiconductors ZnxCd1-xS, Zn I n2S4 and the like, and the photocatalytic hydrogen production performance is improved based on two-photon absorption of WO3 and up-conversion luminescence of rare earth ions. In the composite material, simultaneous transmission of high-energy electrons and photons from the sensitizer to the photocatalyst is realized, and the purpose of hydrogen production by light-light and light-electricity synergistic sensitization photocatalytic reduction of water is achieved. Through the synergistic effect of two-photon absorption of WO3 rich in oxygen vacancies and rare earth ion up-conversion luminescence, the composite material is compounded with the WO3 on the basis of not changing the structure of a photocatalytic semiconductor by adopting a mild method, the composite material can produce hydrogen under ultraviolet-visible-near infrared light illumination, and the solar photocatalytic hydrogen production performance of the composite material is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for expanding the light absorption range of a photocatalytic material and improving the photocatalytic hydrogen production performance, and belongs to the technical field of composite materials. Background Art

[0002] "Energy crisis" and "environmental pollution" are issues of global concern. Producing clean energy instead of traditional fossil fuels through green and environmentally friendly advanced technologies is an effective way to solve energy and environmental problems. In 1972, Fujishima and Honda first reported the breakthrough discovery of TiO2 photocatalytic decomposition of water to produce H2, revealing the possibility of using sunlight to decompose water to produce hydrogen. Photocatalytic technology can convert solar energy into new energy such as hydrogen energy under mild conditions, convert CO2 into high value-added products, and remove organic pollutants and toxic metal ions, bacteria, and viruses in the environment, so it has attracted widespread attention.

[0003] The solar spectrum is composed of 5% ultraviolet light, 45% visible light and 50% near-infrared light. Only photons with energy greater than or equal to the bandgap can cause photocatalytic reactions. The bandgap of common semiconductors is wide, and they can only absorb the energy of ultraviolet light and short-wave visible light, which cannot fully utilize solar energy and limits the photocatalytic activity. Rare earth ions can use the upconversion luminescence process to convert near-infrared light into ultraviolet light and visible light. By combining upconversion luminescent materials with semiconductor photocatalysts, low-energy near-infrared light can be converted into high-energy ultraviolet light and visible light, and then the photocatalyst is excited to produce more photogenerated carriers, thereby achieving the purpose of increasing light utilization. At present, the matrix bandgap of most upconversion luminescent materials is too large and does not have photocatalytic activity. In addition, the composite materials constructed by these matrices and photocatalytic materials often have problems such as mismatch of the valence band position or the inability to form an interface structure that is conducive to photocatalytic reactions, so that the effective utilization of long-wave visible light and near-infrared light cannot be achieved. Summary of the invention

[0004] The present invention dopes rare earth ion Yb into WO3 rich in oxygen vacancies 3+ ,Er 3+ Achieve up-conversion luminescence with WO3:Yb 3+ ,Er 3+ As a sensitizer and photocatalytic semiconductor Zn x Cd 1-xS, Zn In2S4, etc. form a core-shell structure composite material. Based on the two-photon absorption of WO3 and the up-conversion luminescence of rare earth ions, the simultaneous transfer of high-energy electrons and photons from the sensitizer to the photocatalyst is achieved in the composite material, achieving the purpose of light-light and light-electricity synergistic sensitization photocatalytic reduction of water to produce hydrogen. A mild method is used to compound it with the photocatalytic semiconductor without changing its structure. Through the synergistic effect of the two-photon absorption of WO3 rich in oxygen vacancies and the up-conversion luminescence of rare earth ions, the composite material can produce hydrogen under ultraviolet-visible-near-infrared light, significantly improving its solar photocatalytic hydrogen production performance.

[0005] The present invention discloses a method for expanding the light absorption range of photocatalytic materials and improving the photocatalytic hydrogen production performance. First, 5 mL of nitric acid solution is added to 20-25 mL of deionized water and stirred for 10-30 minutes, and 2-4 g of Na2WO4·2H2O is dispersed in 5 mL of deionized water to obtain a Na2WO4 solution. Then, the Na2WO4 solution is slowly added to the HNO3 solution and stirred at room temperature for 10-30 minutes, and then ytterbium nitrate pentahydrate and erbium nitrate hexahydrate are added to the above solution and further stirred for 0.5-1 hour, and the rare earth ions are 1-3 mmol in total, and the ratio of Yb to Er is 1:1-10:1. Subsequently, the mixture is transferred to a stainless steel reactor with a volume of 50 mL and an inner lining of polytetrafluoroethylene, and kept at 180-200°C for 3 hours. After cooling to room temperature (30°C), the yellow product is centrifuged and washed three times with deionized water and ethanol, and then vacuum dried at 60-80°C for 6-12 hours, taken out and ground to obtain WO3:Yb 3+ ,Er 3+ Finally, the obtained WO3:Yb 3+ ,Er 3+ The powder is placed in a muffle furnace and annealed at 300-350℃ in air atmosphere. 3+ ,Er 3+ The composite with photocatalytic semiconductor was prepared by in-situ growth method. 0.5 Cd 0.5 S, CdS and ZnIn2S4 three photocatalytic semiconductors required precursors and WO3:Yb 3+ ,Er 3+ The mixture was placed in a beaker containing 30-50 mL of deionized water at a ratio of 1%-15wt%, stirred at room temperature for 1-2 hours, washed with water and ethanol three times, and dried in a vacuum oven at 60°C for 6-12 hours to obtain a composite material.

[0006] Compared with the prior art, the present invention has the following beneficial effects:

[0007] Rare earth is doped into WO3 rich in oxygen vacancies to obtain two-photon absorption and upconversion luminescence, and it is used as a photosensitizer to form a core-shell structure composite material with a photocatalytic semiconductor by an in-situ growth method. On the one hand, the light response range can be expanded to the visible and near-infrared regions. On the other hand, the heterogeneous structure helps to improve the utilization rate of photogenerated charges, thereby enhancing the photocatalytic hydrogen production performance. The prepared composite photocatalytic material has an absorption spectrum covering the ultraviolet-visible-near-infrared light region and has excellent photocatalytic hydrogen evolution performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0008] Figure 1 Zn 0.5 Cd 0.5 S, WO3 / Zn 0.5 Cd 0.5 S and WO3:Yb 3+ ,Er 3+ / Zn 0.5 Cd 0.5 S XRD pattern.

[0009] Figure 2 WO3:Yb 3+ ,Er 3+ SEM image of .

[0010] Figure 3 WO3:Yb 3+ ,Er 3+ / Zn 0.5 Cd 0.5 SEM image of S.

[0011] Figure 4 Zn 0.5 Cd 0.5 S, WO3 / Zn 0.5 Cd 0.5 S and WO3:Yb 3+ ,Er 3+ / Zn 0.5 Cd 0.5 The absorption spectrum of S.

[0012] Figure 5 Zn 0.5 Cd 0.5 S, WO3 / Zn 0.5 Cd 0.5 S and WO3:Yb 3+ ,Er 3+ / Zn 0.5 Cd 0.5 Photocatalytic hydrogen production performance of S. DETAILED DESCRIPTION

[0013] Example 1. First, 5 mL of nitric acid solution was added to 25 mL of deionized water and stirred for 10 minutes. 3.2 g of Na2WO4·2H2O was dispersed in 5 mL of deionized water to obtain a Na2WO4 solution. Then, the Na2WO4 solution was slowly added to the HNO3 solution and stirred at room temperature. Then, ytterbium nitrate pentahydrate and erbium nitrate hexahydrate were added to the above solution and further stirred for 1 hour. The total amount of rare earth ions was 2 mmol. Subsequently, the mixture was transferred to a 50 mL polytetrafluoroethylene-lined stainless steel reactor and kept at 180°C for 3 hours. After cooling to room temperature, the yellow product was centrifuged and washed three times with deionized water and ethanol. After that, it was taken out and ground after vacuum drying at 60°C for 6 hours to obtain WO3:Yb 3+ ,Er 3+ Finally, the obtained WO3:Yb 3+ ,Er 3+ The powder was placed in a muffle furnace and annealed at 350°C in air atmosphere. 3+ ,Er 3+ / Zn 0.5 Cd 0.5 S was prepared by in-situ growth method, 0.128g CdCl2·2.5H2O, 0.076g ZnCl2, 1.32g Na2S·9H2O and 10mg WO3:Yb 3+ ,Er 3+ Put it into a beaker containing 30 mL of deionized water and stir it at room temperature for 1 hour. Then wash it with water and ethanol three times and dry it in a vacuum oven at 60°C for 12 hours. 3+ ,Er 3+ / Zn 0.5 Cd 0.5 S composite material.

[0014] Example 2. First, 5 mL of nitric acid solution was added to 25 mL of deionized water and stirred for 10 minutes, and 2 g of Na2WO4·2H2O was dispersed in 5 mL of deionized water to obtain a Na2WO4 solution. Then, the Na2WO4 solution was slowly added to the HNO3 solution and stirred at room temperature, and then ytterbium nitrate pentahydrate and erbium nitrate hexahydrate were added to the above solution and further stirred for 0.5 hours, with a total of 2 mmol of rare earth ions. Subsequently, the mixture was transferred to a 50 mL polytetrafluoroethylene-lined stainless steel reactor and kept at 180°C for 10 hours. After cooling to room temperature, the yellow product was centrifuged and washed three times with deionized water and ethanol, and then vacuum dried at 60°C for 6 hours, taken out and ground to obtain WO3:Yb 3+ ,Er 3+ Finally, the obtained WO3:Yb 3+ ,Er 3+The powder was placed in a muffle furnace and annealed at 350°C in air atmosphere. 3+ ,Er 3+ / Zn 0.5 Cd 0.5 S was prepared by in-situ growth method, 0.128g CdCl2·2.5H2O, 0.076g ZnCl2, 1.32g Na2S·9H2O and 20mg WO3:Yb 3+ ,Er 3+ Put it into a beaker containing 30 mL of deionized water and stir it at room temperature for 1 hour. Then wash it with water and ethanol three times and dry it in a vacuum oven at 60°C for 12 hours. 3+ ,Er 3+ / Zn 0.5 Cd 0.5 S composite material.

[0015] Example 3. First, 5 mL of nitric acid solution was added to 25 mL of deionized water and stirred for 10 minutes, and 3.2 g of Na2WO4·2H2O was dispersed in 5 mL of deionized water to obtain a Na2WO4 solution. Then, the Na2WO4 solution was slowly added to the HNO3 solution and stirred at room temperature, and then ytterbium nitrate pentahydrate and erbium nitrate hexahydrate were added to the above solution and further stirred for 1 hour, with a total of 2 mmol of rare earth ions. Subsequently, the mixture was transferred to a 50 mL polytetrafluoroethylene-lined stainless steel reactor and kept at 200°C for 3 hours. After cooling to room temperature, the yellow product was centrifuged and washed three times with deionized water and ethanol, and then vacuum dried at 60°C for 6 hours, taken out and ground to obtain WO3:Yb 3+ ,Er 3+ Finally, the obtained WO3:Yb 3+ ,Er 3+ The powder was placed in a muffle furnace and annealed at 350°C in air atmosphere. 3+ ,Er 3+ / Zn 0.5 Cd 0.5 S was prepared by in-situ growth method, 0.128g CdCl2·2.5H2O, 0.076g ZnCl2, 1.32g Na2S·9H2O and 5mg WO3:Yb 3+ ,Er 3+ Put it into a beaker containing 30 mL of deionized water and stir it at room temperature for 1 hour. Then wash it with water and ethanol three times and dry it in a vacuum oven at 60°C for 12 hours. 3+ ,Er 3+ / Zn 0.5 Cd 0.5 S composite material.

[0016] Example 4. First, 5 mL of nitric acid solution was added to 20 mL of deionized water and stirred for 10 minutes, and 3.2 g of Na2WO4·2H2O was dispersed in 5 mL of deionized water to obtain a Na2WO4 solution. Then, the Na2WO4 solution was slowly added to the HNO3 solution and stirred at room temperature, and then ytterbium nitrate pentahydrate and erbium nitrate hexahydrate were added to the above solution and further stirred for 1 hour, with a total of 2 mmol of rare earth ions. Subsequently, the mixture was transferred to a 50 mL polytetrafluoroethylene-lined stainless steel reactor and kept at 200°C for 3 hours. After cooling to room temperature, the yellow product was centrifuged and washed three times with deionized water and ethanol, and then vacuum dried at 60°C for 6 hours, taken out and ground to obtain WO3:Yb 3+ ,Er 3+ Finally, the obtained WO3:Yb 3+ ,Er 3+ The powder was placed in a muffle furnace and annealed at 350°C in air atmosphere. 3+ ,Er 3+ / Zn 0.5 Cd 0.5 S was prepared by in-situ growth method, 0.128g CdCl2·2.5H2O, 0.076g ZnCl2, 1.32g Na2S·9H2O and 15mg WO3:Yb 3+ ,Er 3+ Put it into a beaker containing 30 mL of deionized water and stir it at room temperature for 1 hour. Then wash it with water and ethanol three times and dry it in a vacuum oven at 60°C for 12 hours. 3+ ,Er 3+ / Zn 0.5 Cd 0.5 S composite material.

[0017] Example 5. First, add 5 mL of nitric acid solution to 25 mL of deionized water and stir for 10 minutes, and disperse 3.2 g of Na2WO4·2H2O in 5 mL of deionized water to obtain Na2WO4 solution. Then slowly add the Na2WO4 solution to the HNO3 solution and stir at room temperature, and then slowly add the Na2WO4 solution to the HNO3 solution and stir at room temperature. Subsequently, transfer the mixture to a 50 mL polytetrafluoroethylene-lined stainless steel reactor and keep it at 180°C for 3 hours. After cooling to room temperature, centrifuge the yellow product and wash it three times with deionized water and ethanol, then vacuum dry it at 60°C for 6 hours, take it out and grind it to obtain WO3 powder. Finally, put the obtained WO3 powder into a muffle furnace and anneal it at 350°C in an air atmosphere. WO3 / Zn 0.5 Cd 0.5S was prepared by in-situ growth method. 0.128g CdCl2·2.5H2O, 0.076g ZnCl2, 1.32g Na2S·9H2O and 10mg WO3 were placed in a beaker containing 30mL deionized water and stirred at room temperature for 1 hour. Then it was washed with water and ethanol three times and dried in a vacuum oven at 60℃ for 12 hours. WO3 / Zn 0.5 Cd 0.5 S composite material.

[0018] Example 6. First, 5 mL of nitric acid solution was added to 25 mL of deionized water and stirred for 10 minutes, and 3.2 g of Na2WO4·2H2O was dispersed in 5 mL of deionized water to obtain a Na2WO4 solution. Then, the Na2WO4 solution was slowly added to the HNO3 solution and stirred at room temperature, and then ytterbium nitrate pentahydrate and erbium nitrate hexahydrate were added to the above solution and further stirred for 1 hour, with a total of 2 mmol of rare earth ions. Subsequently, the mixture was transferred to a 50 mL polytetrafluoroethylene-lined stainless steel reactor and kept at 180°C for 3 hours. After cooling to room temperature, the yellow product was centrifuged and washed three times with deionized water and ethanol, and then vacuum dried at 60°C for 6 hours, taken out and ground to obtain WO3:Yb 3+ ,Er 3+ Finally, the obtained WO3:Yb 3+ ,Er 3+ The powder was placed in a muffle furnace and annealed at 350°C in air atmosphere. 3+ ,Er 3+ / CdS was prepared by in-situ growth method. 0.256g CdCl2·2.5H2O, 1.32g Na2S·9H2O and 10mg WO3:Yb 3+ ,Er 3+ Put it into a beaker containing 30 mL of deionized water and stir it at room temperature for 1 hour. Then wash it with water and ethanol three times and dry it in a vacuum oven at 60°C for 12 hours. 3+ ,Er 3+ / CdS composite materials.

[0019] Example 7. First, 5 mL of nitric acid solution was added to 25 mL of deionized water and stirred for 10 minutes, and 3.2 g of Na2WO4·2H2O was dispersed in 5 mL of deionized water to obtain a Na2WO4 solution. Then, the Na2WO4 solution was slowly added to the HNO3 solution and stirred at room temperature, and then ytterbium nitrate pentahydrate and erbium nitrate hexahydrate were added to the above solution and further stirred for 1 hour, with a total of 2 mmol of rare earth ions. Subsequently, the mixture was transferred to a 50 mL polytetrafluoroethylene-lined stainless steel reactor and kept at 180°C for 3 hours. After cooling to room temperature, the yellow product was centrifuged and washed three times with deionized water and ethanol, and then vacuum dried at 60°C for 6 hours, taken out and ground to obtain WO3:Yb 3+ ,Er 3+ Finally, the obtained WO3:Yb 3+ ,Er 3+ The powder was placed in a muffle furnace and annealed at 350°C in air atmosphere. 3+ ,Er 3+ / ZnIn2S4 was prepared by in-situ growth method, 0.11gZnCl2, 0.35gInCl3, 1.32gNa2S·9H2O and 10mgWO3:Yb 3+ ,Er 3+ Put it into a beaker containing 30 mL of deionized water and stir it at room temperature for 1 hour. Then wash it with water and ethanol three times and dry it in a vacuum oven at 60°C for 12 hours. 3+ ,Er 3+ / ZnIn2S4 composite materials.

[0020] The following experiments were used to verify the effect of the present invention:

[0021] A core-shell structure of WO3:Yb prepared by the present invention 3+ ,Er 3+ / Zn 0.5 Cd 0.5 S materials were characterized by XRD ( Figure 1 ), SEM( Figure 2 , Figure 3 ), DRS characterization ( Figure 4 ) and photocatalytic hydrogen production performance test ( Figure 5 ). WO3:Yb 3+ ,Er 3+ / Zn 0.5 Cd 0.5 The XRD characteristic peak positions of S materials are similar to those of WO3 and Zn 0.5 Cd 0.5 S material is consistent with XRD standard card. Figure 2 and Figure 3WO3:Yb 3+ ,Er 3+ and WO3:Yb 3+ ,Er 3+ / Zn 0.5 Cd 0.5 The SEM image of S clearly shows the formation of uniform flake WO3:Yb 3+ ,Er 3+ and WO3:Yb 3+ ,Er 3+ / Zn 0.5 Cd 0.5 S core-shell structure. Figure 4 It shows that the light absorption of the composite photocatalytic material covers the ultraviolet-visible-near infrared region. Figure 5 It shows that with Zn 0.5 Cd 0.5 S and WO3 / Zn 0.5 Cd 0.5 Compared with S, WO3:Yb 3+ ,Er 3+ / Zn 0.5 Cd 0.5 S has higher photocatalytic hydrogen production performance under simulated sunlight irradiation.

Claims

1. A method for expanding the light absorption range of a photocatalytic material to improve the photocatalytic hydrogen production performance, characterized in that: First, nitric acid solution is added to deionized water and stirred, and Na2WO4·2H2O is dispersed in deionized water to obtain Na2WO4 solution; then, the Na2WO4 solution is slowly added to the HNO3 solution and stirred at room temperature, and then ytterbium nitrate pentahydrate and erbium nitrate hexahydrate are added to the above solution and further stirred; then, the mixture is transferred to a stainless steel reactor lined with polytetrafluoroethylene for insulation, and then cooled to room temperature, the yellow product is centrifuged and washed three times with deionized water and ethanol, and then dried and ground to obtain WO3:Yb 3+ ,Er 3+ Powder; Finally, the obtained WO3:Yb 3+ ,Er 3+ The powder was placed in a muffle furnace for annealing; WO3:Yb 3+ ,Er 3+ The composite with photocatalytic semiconductor was prepared by in-situ growth method. 0.5 Cd 0.5 S, CdS and ZnIn2S4 three photocatalytic semiconductors required precursors and WO3:Yb 3+ ,Er 3+ The mixture is placed in a beaker containing 30-50 mL of deionized water in an appropriate proportion and stirred at room temperature for 1-2 hours; then washed with water and ethanol for three times and dried in a vacuum oven at 60° C. for 6-12 hours to obtain a composite material.

2. A method for expanding the light absorption range of a photocatalytic material to improve the photocatalytic hydrogen production performance according to claim 1, characterized in that: Add 5 mL of nitric acid solution to 20-25 mL of deionized water and stir for 10-30 minutes.

3. The method of expanding the light absorption range of photocatalytic materials to improve photocatalytic hydrogen production performance according to claim 1, characterized in that: Disperse 2-4 g of Na2WO4·2H2O in 5 mL of deionized water to obtain a Na2WO4 solution.

4. The method of expanding the light absorption range of photocatalytic materials to improve photocatalytic hydrogen production performance according to claim 1, characterized in that: The stirring time is 0.5-1 hour.

5. The method of expanding the light absorption range of photocatalytic materials to improve photocatalytic hydrogen production performance according to claim 1, characterized in that: The total amount of rare earth ions is 1-3 mmol, and the ratio of Yb to Er is 1:1-10:

1.

6. The method of expanding the light absorption range of photocatalytic materials to improve photocatalytic hydrogen production performance according to claim 1, characterized in that: The volume of the reactor is 50-100 mL, and the mixture is kept at 180-200° C. in the reactor for 3 hours.

7. The method of expanding the light absorption range of photocatalytic materials to improve photocatalytic hydrogen production performance according to claim 1, characterized in that: The mixture was dried under vacuum at 60-80°C for 6-12 hours and then taken out and ground.

8. The method of expanding the light absorption range of photocatalytic materials to improve photocatalytic hydrogen production performance according to claim 1, characterized in that: The annealing treatment is carried out in an air atmosphere at 300-350°C.

9. The method of expanding the light absorption range of photocatalytic materials to improve photocatalytic hydrogen production performance according to claim 1, characterized in that: The photocatalytic semiconductor can be Zn 0.5 Cd 0.5 S, CdS, ZnIn2S4 or other materials that can be used with WO3:Yb 3+ ,Er 3+ Semiconductors that form suitable heterostructures.

10. The method of expanding the light absorption range of photocatalytic materials to improve photocatalytic hydrogen production performance according to claim 1, characterized in that: WO3:Yb 3+ ,Er 3+ With Zn 0.5 Cd 0.5 The proportion of S, CdS, and ZnIn2S4 semiconductors is 1%-15wt%.

Citation Information

Patent Citations

  • Photoactive material

    CA2812031A1

  • Red light or infrared light catalytic material comprising semiconductor material and up-conversion material

    CN101642702A

  • Preparation method and application of Z-type WO3:Yb&lt;3+&gt;,Er&lt;3+&gt; / Ag / Ag3VO4 / Ag photocatalyst

    CN113019365A

  • Zn0. 5Cd0. 5S / WO3 heterojunction multifunctional photocatalyst and preparation method thereof

    CN117414849A

  • Preparation method of spherical W18O49 material

    CN117566800A